2015
DOI: 10.5152/dir.2014.14036
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolization with yttrium-90 resin microspheres for neuroendocrine tumor liver metastases

Abstract: RESULTSThe mean follow-up was 23.0±19.4 months and the median overall survival was 39 months (95% CI, 12.6-65.4 months), with one-and two-year survival rates of 71% and 45%, respectively. Imaging follow-up using RECIST at three-month intervals demonstrated partial response in 43%, complete remission in 3%, stable disease in 37%, and progressive disease in 17% of patients. Extent of tumor involvement was found to have a statistically significant influence on overall survival (P = 0.03). The existence of extrahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 35 publications
2
17
1
2
Order By: Relevance
“…Of note, all patients in this group had a variety of treatments before 90 Y treatment, including somatostatin analogs, surgical lobectomy, chemotherapy, TAE/TACE, RFA, molecularly targeted drugs, and external irradiation. Some reported disease control rates of different treatments for unresectable liver metastases of NET range from 40.7% to 53% for chemotherapy, from 50% to 100% for TAE/TACE, and from 64.7% to 96.4% for 90 Y therapy . TAE/TACE and 90 Y treatments have a similar disease control rate, both of which were better than that of chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, all patients in this group had a variety of treatments before 90 Y treatment, including somatostatin analogs, surgical lobectomy, chemotherapy, TAE/TACE, RFA, molecularly targeted drugs, and external irradiation. Some reported disease control rates of different treatments for unresectable liver metastases of NET range from 40.7% to 53% for chemotherapy, from 50% to 100% for TAE/TACE, and from 64.7% to 96.4% for 90 Y therapy . TAE/TACE and 90 Y treatments have a similar disease control rate, both of which were better than that of chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Many factors were reported to relate the overall survival in patients who had metastatic liver NET, including ECOG performance score, bilirubin, hepatic tumor burden, prior surgery, size of target lesions, baseline chemistry values, Ki‐67 index, presence of extrahepatic disease, and ability to deliver a specified dose . To our knowledge, this study is the first to show that Child–Pugh B class and positive lymph node metastases are associated with reduced overall survival for metastatic NET to liver after radioembolization.…”
Section: Discussionmentioning
confidence: 70%
“…Bei Patienten mit signifikanter extrahepatischer Metastasierung sollte die RE möglichst nicht zur Anwendung kommen, da diese methodenimmanent nur die hepatische Tumorlast behandeln kann [558]. Bei Patienten, bei denen die hepatische Tumorlast jedoch voraussichtlich die weitere Prognose bestimmt und die extrahepatische Tumorlast prognostisch nicht relevant ist ("liverdominant disease"), kann eine RE zur Anwendung kommen und sinnvoll sein [558,659]. Die Studienergebnisse hierzu sind limitiert, allerdings war beispielsweise bei Peker et al eine extrahepatische Metastasierung kein prognostisch ungünstiger Faktor [659].…”
Section: Empfehlung Starker Konsensunclassified
“…The largest series by Kennedy [ 25 ] showed a PR in 61% of the patients with low toxicities, mainly fatigue (6.5%). A recent study by Peker et al [ 26 ] demonstrated the safety and effectiveness of the treatment of unresectable liver NET, with 1- and 2-year survival rates of 71 and 45%, respectively. A recent meta-analysis by Devcic et al [ 27 ] showed an average objective response of 50% and a weighted average disease control rate of 86%.…”
Section: Resultsmentioning
confidence: 99%